Evaluating contaminated dental aerosol and splatter in an open plan clinic environment: Implications for the COVID-19 pandemic. (February 2021) - Holliday, Richard; Allison, James R.; Currie, Charlotte C.; Edwards, David C.; Bowes, Charlotte; Pickering, Kimberley; Reay, Sarah; Durham, Justin; Lumb, Joanna; Rostami, Nadia; Coulter, Jamie; Nile, Christopher; et al.
Abstract: Objectives: Identify splatter/aerosol distribution from dental procedures in an open plan clinic and explore aerosol settling time after dental procedures. Methods: In two experimental designs using simulated dental procedures on a mannequin, fluorescein dye was introduced: (1) into the irrigation system of an air-turbine handpiece; (2) into the mannequin's mouth. Filter papers were placed in an open plan clinic to collect fluorescein. An 8-metre diameter rig was used to investigate aerosol settling time. Analysis was by fluorescence photography and spectrofluorometry. Results: Contamination distribution varied across the clinic depending on conditions. Unmitigated procedures have the potential to deposit contamination at large distances. Medium volume dental suction (159 L/min air) reduced contamination in the procedural bay by 53%, and in other areas by 81-83%. Low volume suction (40 L/min air) was similar. Cross-ventilation reduced contamination in adjacent and distant areas by 80-89%. In the most realistic model (fluorescein in mouth, medium volume suction), samples in distant bays (≥5 m head-to-head chair distance) gave very low or zero readings (< 0.0016% of the fluorescein used during the procedure). Almost all (99.99%) of the splatter detected was retained within the procedural bay/walkway. After 10 min, very little additional aerosol settled. Conclusions: Cross-infection risk from dental procedures in an open plan clinic appears small when bays are ≥ 5 m apart. Dilution effects from instrument water spray were observed, and dental suction is of benefit. Most settled aerosol is detected within 10 min indicating environmental cleaning may be appropriate after this. Clinical Significance: Aerosols produced by dental procedures have the potential to contaminate distant sites and the majority of settled aerosol is detectable after 10 min. Dental suction and ventilation have a substantial beneficial effect. Contamination is likely to be minimal in open plan clinics at distances of 5 m or more.